Piezodynamic Eradication of Both Gram-Positive and Gram-Negative Bacteria by Using a Nanoparticle Embedded Polymeric Membrane - Chan Chen; Shubham Roy; Jingjing Wang; Xiafen Lu; Siyi Li; Hao Yang; Minggang Cheng; Bing Guo; Yuzhong Xu (MDPI AG, 2023)
Nowadays, bacterial infection is regarded as a serious threat to humankind, which needs to be taken care of. The emergence of antibiotic resistance and multidrug resistance (MDR) is rendering this situation more troublesome. However, several alternative treatment regimens have aided such diseases quite well in the recent past, among which dynamic antibacterial therapies combat this situation quite well. Among various dynamic therapies, piezodynamic therapy is a very recent avenue, in which mechanical stimuli have been exploited to treat bacterial infections. Herein, piezo-active bismuth ferrite-loaded poly(vinylidene fluoride-co-hexafluoropropylene) polymer has been utilized to eradicate gram-positive bacteria (E. faecalis) and gram-negative bacteria (E. coli). The sample has been designed in a free-standing membrane form, which, under soft ultrasound (~10 kHz), generates reactive radicals to ablate bacteria. Initially, the structure and morphology of the membrane have been substantiated by using X-ray diffraction and scanning electron microscopy methods; besides, Fourier transform infrared spectrum of the sample depicts a tremendously high value of polarizability and further confirms the piezo-activity of the membrane. More than 99% of E. coli and E. faecalis have been successfully eradicated within 30 min of ultrasound. Moreover, the solid-state structure and hydrophobic nature of the membrane help us to reuse it in a cyclic manner, which is possibly reported herein for the very first time. This novel membrane could be deployed in healthcare systems and pigment industries and could be exploited as a self-cleaning material.